2004
DOI: 10.1002/gps.1093
|View full text |Cite
|
Sign up to set email alerts
|

Life long changes in cognitive ability are associated with prescribed medications in old age

Abstract: Clinically, the degree to which drugs impair cognition in relatively fit, older people may not be apparent. However, in population terms, medication use, particularly polypharmacy, is important. Statins, used as currently indicated for cardiovascular disease, appear promising in ameliorating cognitive decline in older people. However, firm recommendation of their use should await the outcome of ongoing randomised clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 42 publications
0
31
0
Order By: Relevance
“…The reverse was true for participants who were not using statins at age 80 years 68. Notably, a report that analysed primary care EMR data from the QResearch database (England and Wales) found no elevated risk of dementia among new users of statins (who entered the cohort on receipt of their first statin prescription) during follow-up compared with participants who did not use statins during the follow-up period, although the results suggested that the risk of dementia was reduced with simvastatin or atorvastatin use in women 63.…”
Section: Observational Studiesmentioning
confidence: 99%
“…The reverse was true for participants who were not using statins at age 80 years 68. Notably, a report that analysed primary care EMR data from the QResearch database (England and Wales) found no elevated risk of dementia among new users of statins (who entered the cohort on receipt of their first statin prescription) during follow-up compared with participants who did not use statins during the follow-up period, although the results suggested that the risk of dementia was reduced with simvastatin or atorvastatin use in women 63.…”
Section: Observational Studiesmentioning
confidence: 99%
“…With the high regulatory level of CB1 receptors on various neurotransmitters in the cingulate cortex, it is logical to deduce that there could be a connection between CB1 receptor activity being restored and an improved level of anxiety levels due to simvastatin treatment. Simvastatin's potential ameliorative properties upon cognitive decline have been suggested in past cohort studies in older people [48].…”
Section: Simvastatin Attenuated the Declined Cb1 Receptor Expressionsmentioning
confidence: 99%
“…For self-reported health, participants were interviewed (by trained researchers) specifically about vascular (cardiovascular and cerebrovascular) problems, cancer, hypertension, diabetes, thyroid dysfunction and dementia as described previously [33]. They were then asked to state if they had any other diseases not mentioned.…”
Section: Health Statusmentioning
confidence: 99%